Migraine, tension-type headache, and depression among Saudi female students in Taif University - Dalia E. Desouky; Hany A. Zaid; Azza A. Taha (SpringerOpen, 2019)
Abstract Background Studies done in Saudi Arabia showed a high prevalence of headache among university students. Limited research was done to assess the relationship between headache and psychiatric disorders. The aim of this study was to assess the prevalence and association between migraine, tension-type headache, and depression among Saudi female students in Taif University. Participants and methods A cross-sectional study using self-administered questionnaires about headache and depression was conducted at the Taif University on 1340 female students in the academic year 2016-2017. The Beck Depression Inventory, the ID Migraine™ screening tool, and the criteria of the International Headache Society were used to investigate the depressive symptoms and headache types. Results The self-reported headache prevalence was 68.4%, and the prevalence of migraine, tension-type headache (TTH), and depression was 32.5%, 29.5%, and 6.2%, respectively. The main migraine trigger was stress or anxiety; 86.6% of migraineurs had a positive family history, and only 11.9% sought medical care for headache. Of students with TTH, 61.1% reported family history and only 12.4% sought medical care. Paracetamol was the commonly used analgesic for all headache types. Medical students and students in older grades showed significantly higher levels of all headache types. Depression prevalence was significantly higher among migraineurs and students who suffered higher headache frequencies. Conclusion The study demonstrated a high prevalence of headache among the studied students and an association between headache and depression. The study calls for increasing awareness towards headache and the importance of seeking medical consultation. Management strategies should be planned for the observed headache and depression comorbidity.